Efforts to Foster Students' Attitude of Independence Through Islamic Entrepreneurship Activities at Al-Aziz Islamic Boarding School - Hikayat, Bunga Anisa; Fakhruddin, Agus; Subakti, Ganjar Eka (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2024)
The goals of Islamic Religious Education (PAI) are in principle in line with the character values developed by the government, one of which is the value of independence. Therefore, PAI has a role as a means for the realization of these character values. Regarding the increase in the number of unemployed based on education levels that are not in accordance with ideal conditions, it is a phenomenon that is quite concerning. Based on data from the Central Statistics Agency (BPS), shows that until February 2024, the unemployment rate at the vocational and high school levels is still the largest contributor to unemployment compared to graduates from other education levels. Therefore, the attitude of student independence needs to be maximized. Just as the Prophet (saw) became an entrepreneur for ± 25 years and became an exemplary example for his people to form an attitude of independence from a young age. This research generally aims to describe efforts to foster independence attitudes through Islamic entrepreneurship at Al-Aziz Islamic Boarding School High School. This research is important to be carried out as a reference for efforts to reduce the unemployment rate and improve the quality of students so that they become useful human beings and have a strong survival of life. This research uses a qualitative approach and a case study method with data collection techniques, namely observation, interview, and documentation. The results of the study show that the Islamic entrepreneurship program at Al-Aziz IBS High School has succeeded in shaping students' attitudes of independence in accordance with six indicators of independence in a person.